Exploiting PET-RAFT polymerization mediated by cross-linked zinc porphyrins for the thermo-sensitive regulation of poly(N-isopropylacrylamide-b-acrylamide). (5th September 2022) - Li, Fanfan; Yu, Yi; Lv, Hanyu; Wan, Yameng; Gao, Xiaoqiang; Li, Yanxun; Zhang, Yanwu
Graphical abstract: Highlights: P(NIPAm-b-AM) is prepared via PET-RAFT polymerization mediated by ZnTHP-Me2 Si. DFT study find that ZnTHP-Me2 Si possesses excellent catalytic activity. The thermo-sensitive of P(NIPAm-b-AM) can be tuned by regulating the AM content. H-bonding interaction between P(NIPAm-b-AM) and H2 O is enhanced as AM content increases. Abstract: A series of thermo-sensitive block copolymers poly(N-isopropylacrylamide-b-acrylamide) (P(NIPAm-b-AM)) are prepared via photoinduced electron/energy transfer-reversible addition-fragmentation chain transfer (PET-RAFT) polymerization mediated by the cross-linked zinc porphyrins (ZnTHP-Me2 Si) with superior photo-catalytic properties using one-pot method. The thermal transition temperatures of P(NIPAm-b-AM) samples are analyzed via lower critical solution temperature (LCST) measurements in water/P(NIPAm-b-AM) mixtures, which show that the thermo-sensitive of P(NIPAm-b-AM) could be tuned by regulating the molar ratio of AM/NIPAm. Very interestingly, when the mole fraction of AM increased from 0 to 0.4, the LCST and water contact angle of P(NIPAm-b-AM) aqueous solution increased linearly, which means the thermo-sensitive polymers with target LCST or hydrophilicity could be prepared by increasing or decreasing AM content. In addition, the hardness of P(NIPAm-b-AM) also enhanced as the AM content increased. According to the density functional theory (DFT) calculations and radial distribution function (RDF) analyses, ZnTHP-Me2 Si has smaller energy gap, and the H-bonding interaction between P(NIPAm-b-AM) and water molecules could be enhanced with increasing AM content. The outcomes of this work open new approaches to develop thermo-sensitive polymers with biocompatibility for the wide applications in highly efficient and controlled drug delivery system.